Reliable majority voter based on spin transfer torque magnetic tunnel junction device. Issue 1 (1st January 2016) - Butzen, P.F.; Slimani, M.; Wang, Y.; Cai, H.; Naviner, L.A.B.
Abstract : A reliable majority voter circuit using a nanometre spin transfer torque magnetic tunnel junction (STT‐MTJ) is presented. The circuit tolerates single transient faults and manages process variations due to technology downscaling. The use of this magnetic device brings non‐volatility memory to logic circuits and promises to overcome the rising standby power issue. By using the STMicroelectronics fully depleted silicon on insulator 28 nm design kit and a precise STT‐MTJ compact model, electrical simulations have been carried out to show its low‐power and high reliability performances.